2022
DOI: 10.5144/0256-4947.2022.359
|View full text |Cite
|
Sign up to set email alerts
|

High COX-2 immunostaining in papillary thyroid carcinoma is associated with adverse survival outcomes

Abstract: BACKGROUND: Thyroid carcinoma is one of the most common malignancies worldwide. More than 70%-80% are papillary thyroid carcinoma (PTC). Many factors influence the PTC pathway of development such as genetic mutations, growth factors, and radiation. More biological understanding of the genetic and molecular pathways is needed in PTC to determine tumor behavior, and initial clinical assessment. OBJECTIVES: Investigate the relation of COX-2 immunostaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…High PTGS2 protein expression in papillary thyroid carcinoma is associated with adverse survival outcomes [35]. However, our bioinformatics analysis showed that the mRNA expression of PTGS2 in normal and tumor tissues was similar, and PTGS2 mRNA expression was not prognostic in thyroid carcinoma (Supplementary Figures S1E, S1F).…”
Section: Discussionmentioning
confidence: 83%
“…High PTGS2 protein expression in papillary thyroid carcinoma is associated with adverse survival outcomes [35]. However, our bioinformatics analysis showed that the mRNA expression of PTGS2 in normal and tumor tissues was similar, and PTGS2 mRNA expression was not prognostic in thyroid carcinoma (Supplementary Figures S1E, S1F).…”
Section: Discussionmentioning
confidence: 83%